2019
DOI: 10.3389/fnagi.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of Cerebral Small Vessel Disease and Age-Related Cognitive Changes

Abstract: Subclinical cerebrovascular disease is frequently identified in neuroimaging studies and is thought to play a role in the pathogenesis of cognitive disorders. Identifying the etiologies of different types of lesions may help investigators differentiate between age-related and pathological cerebrovascular damage in cognitive aging. In this review article, we aim to describe the epidemiology and etiology of various brain magnetic resonance imaging (MRI) measures of vascular damage in cognitively normal, older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 174 publications
(253 reference statements)
4
35
2
3
Order By: Relevance
“…CSVD is very common in elderly patients [16], however, in our study we found a high frequency of these lesions in a group of hypertensive patients with a mean age below 65 years, most of them with low to moderate CVR. Few studies have reported these injuries in non-elderly individuals [-2017], in which WML is the most common injury, as in our study.…”
Section: Intracranial Vascular Injurycontrasting
confidence: 74%
“…CSVD is very common in elderly patients [16], however, in our study we found a high frequency of these lesions in a group of hypertensive patients with a mean age below 65 years, most of them with low to moderate CVR. Few studies have reported these injuries in non-elderly individuals [-2017], in which WML is the most common injury, as in our study.…”
Section: Intracranial Vascular Injurycontrasting
confidence: 74%
“…Different manifestations of CSVD based on neuroimaging findings result in different and overlapping health burden and epidemiology [54]. Increasing age has been reported to elevate the finding of WMHs, lacunes, perivascular spaces, and CMBs in healthy populations [54][55][56]. However, increased vascular risk factors are consistent with the prevalence of CMBs but not in other imaging findings [56,57].…”
Section: Neuroepidemiology and Health Burdenmentioning
confidence: 99%
“…The effects of several manifestations of CSVD on cognition seem to be invariably influenced by the location of the lesion(s). The damaged and reduced white matter integrity in the frontal lobe and its dysfunction are associated with reduced transmission of information to other parts of the brain in the presence of WMHs [54], lacunes (deep nuclear [78.2%], posterior fossa [10.1%]) [66], and perivascular spaces [65,67]. In contrast, temporal lobe lesion is more associated with the findings of lobar and deep CMBs [68,69].…”
Section: Neuroepidemiology and Health Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…Лейкоареоз (изменения белого вещества, сосудистая лейкоэнцефалопатия) представляет собой зоны увеличенного сигнала от белого вещества мозга в Т2и FLAIR-режимах, чаще локализующиеся перивентрикулярно или в глубинных отделах лобных долей. Б М С и К Н В большинстве исследований показано, что БМС обычно сопряжена с КН, не достигающими выраженности деменции [33][34][35][36][37]. Вероятно, КН являются наиболее ранним следствием БМС.…”
unclassified